Synthesis of some heterocyclic derivatives of 1,8-Naphthyridine with a new substitution on the Naphthyridine ring (Baghdad Science Journal, 2025)
Abstract The Synthesis in good yields of some new 1,8-Naphthyridine derivatives (1-9) and characterized on the basis of IR and 1H NMR spectra data. The compounds (1) and (6) were utilized as a starting material for the preparing of these compounds.